2012
DOI: 10.1371/journal.pone.0040465
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Regulates Hepcidin Expression via GPR30-BMP6-Dependent Signaling in Hepatocytes

Abstract: Hepcidin, a liver-derived iron regulatory protein, plays a crucial role in iron metabolism. It is known that gender differences exist with respect to iron storage in the body; however, the effects of sex steroid hormones on iron metabolism are not completely understood. We focused on the effects of the female sex hormone estrogen on hepcidin expression. First, ovariectomized (OVX) and sham-operated mice were employed to investigate the effects of estrogen on hepcidin expression in an in vivo study. Hepcidin ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
4
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(120 citation statements)
references
References 36 publications
4
111
4
1
Order By: Relevance
“…Namely, a functional ERE within the promoter of FPN was responsible for the suppressive effect induced by E2. Our results offered an additional explanation for enhanced body iron storage in postmenopausal women [22]. In support of this statement, our results revealed that the expression of hepatic FPN was elevated in OVX mice, compared to SHAM mice.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Namely, a functional ERE within the promoter of FPN was responsible for the suppressive effect induced by E2. Our results offered an additional explanation for enhanced body iron storage in postmenopausal women [22]. In support of this statement, our results revealed that the expression of hepatic FPN was elevated in OVX mice, compared to SHAM mice.…”
Section: Discussionsupporting
confidence: 86%
“…The current findings would be beneficial to explain increased body iron mass in post-menopausal women. Our research group and another group have identified the regulation of hepcidin expression by estrogen [22,23]. Our previous data characterized an inhibitory effect of estrogen on hepcidin expression via a functional ERE within its promoter [23].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…This location differs from the one between −2474 and −2462 reported by the previous study (Yang et al, 2012). However, Ikeda and colleagues recently described different findings that the OVX mice revealed decreased hepcidin expression in livers, which was attributed to another mechanism of estrogen signaling in regulating hepcidin expression through G-coupled protein 30 (GPR30)-bone morphologic protein 6 (BMP6)-dependent pathway (Ikeda et al, 2012). The classical ERs and GPR30 are co-expressed in many types of cells and tissues, and the combined effect of estrogen on ERs and GPR30 is distinct, depending on a manner of synergism or antagonism (Prossnitz and Maggiolini, 2009).…”
Section: Elevated Hepcidin Expression In Liver Devoid Of Endogenous Econtrasting
confidence: 57%